The second wave of COVID-19 disease in hemodialysis patients: An experience of a dialysis center from Pakistan - Dhrolia, Murtaza; Rahim, Shabana; Ahmad, Aasim (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate the characteristics and outcomes of second wave of coronavirus disease-2019 in haemodialysis patients. Method: The retrospective, observational cohort study was conducted at The Kidney Center Post-Graduate-Training-Institute, Karachi, Pakistan and comprised data of patients regardless of gender who contracted coronavirus disease-2019 during the second wave from November 3, 2020, till February 12, 2021. Epidemiological, clinical, laboratory, and radiological characteristics and outcomes the patients were reviewed. Data was analysed using SPSS 21. Results: Of 437 patients on haemodialysis, 46(10.5%) contracted coronavirus disease-2019; 29(63%) males and 17(37%) females. The overall median age was 61.5+/-13.02 years. Most patients developed mild disease 27(%). The most common symptom was fever 29(63%), and 6(13.1%) patients had patchy bilateral opacity on chest radiograph. Major complications were lymphocytopenia 29(63%), pneumonia 15(32.6%), thrombocytopenia 8(17.4%), and septic shock 5(10.9%). Overall, 15(32.6%) patients required hospitalisation, and 8(17.4%) required mechanical ventilation. There were 13(28.3%) deaths. Patients aged >60 years had 6.8 times more severe disease (p=0.023) and chances of death among them were 5.8 times higher (p=0.036) than in those aged <60 years. Conclusion: There was a high susceptibility of haemodialysis patients during the second wave of coronavirus disease compared to the general population. The most important determinants of death were advanced age, lower oxygen saturation and thrombocytopenia at presentation. Key Words: Second wave Covid-19, Clinical characteristics, Outcome, Haemodialysis.